Characterisation of Lacticaseibacillus rhamnosus Isolated from Naturally Fermented Milk Product Samples of Tribal Regions of Thiruvananthapuram District of Kerala - Rejeesh R; Beena AK; Ligimol James; Sudheerbabu P; Rajakumar S N; Rachana C R; Vinod Viswanath (The Indian Veterinary Journal, 2023)
The out spread of pandemic has created an awareness in general public regarding the importance of functional foods and leading to a steep increase in the consumption of fermented dairy products. Naturally fermented foods are always a niche of many useful organism with immense functional properties, but less explored. The lactic acid bacteria, Lcb.rhamnosus AMB 120 isolated from the thayir samples collected from tribal belt of Thiruvananthapuram district of Kerala is assessed for its physico techno textural, functional and safety attributes. The organism showed matching results with Lacticaseibacillus rhamnosus GG especially the antibiotic susceptibility, adhesion and aggregation properties. This organism had resulted attributes such as antioxidant activity, cell surface hydrophobicity and auto aggregation in the range of 61%, 77.94% and 60.6% respectively. With many listed probiotics, this organism can also be considered as a potential candidate for manufacturing fermented functional products and cheese in food industry.